COVID-19 impact on bladder cancer treatment - Fabrício Kaminagakura; Marcos F. Dall'Oglio; José A. da Silva Jr.; Klebson Rodrigues-Barbosa; Jorge Ocké; Luiz J. Budib (Urología Colombiana)
Objective: The proposed study aims to present the experience with radical cystectomy from a urology service in a public teaching, non-profit hospital with a medical residency service, during the COVID-19 pandemic period in 2020. Materials and methods: We led a prospective study from February 2020 to October 2020, in which three 2nd-year urology residents, guided by one particular attending physician, performed 20 radical cystectomies in an acute public hospital. Results: Most patients were male, with Muscle-invasive bladder cancer being the major indication in our sample. There was a meaningful and direct correlation between surgical time and length of stay in the Intensive Care Unit. Conclusion: Despite the complexity of the surgery, the execution of radical cystectomies during a pandemic period is feasible, with positive surgical results and complication rates compatible with the current literature.